SEJARAH PERTAMBAGAN BAUKSIT DI KABUPATEN BINTAN PADA TAHUN 1924-2014 - Muhammad Kholik Sudewo; Bedriati Ibrahim; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: Indonesia is a country rich in renewable and non-renewable natural resources, including bauxite, a non-renewable natural resource. In Indonesia there is a large bauxite reserve in Bintan that was first discovered in Bintan. The discovery of bauxite in Bintan is the beginning of the progress of Bintan it self. The purpose of this writing is as follows: (1) The history of bauxite mining in Bintan Regency find out during the colonial period. (2) For the development of bauxite mining in Bintan Regency in the post-independence period (3) To find out the company's contribution to the surrounding community (4) To find out the current state of bauxite mining companies (5) To discover the role of local government in bauxite mining, especially in Bintan Regency. This research uses the historical method referred to by the historical method, an approach that draws attention to earlier research by collecting sources from earlier research that is used as a reference in the history of writing. Research result: (1)Bauxite was first discovered in Bintan in 1924 by a Dutch company, NV NIBEM. The first export of bauxite was in 1935 with the aim of exporting to aluminum-producing countries, In 1942, Dutch bauxite mining was taken over by Furukawa Co.Ltd for 3 years before.(2)It was finally nationalized at Indonesia in 1959 this year is the beginning of development mining.(3)Many facilities provided by PT. ANTAM for example office development and land delegation.(4)In 2009 ANTAM conducted a post-mining program and was followed by private companies in 2014.(5) The government is currently conducting surveillance and contributing to the construction of tourist attractions from teh former mining land of ANTAM.Key Words: History of Bauxite Mining